2014
DOI: 10.1002/biot.201300523
|View full text |Cite
|
Sign up to set email alerts
|

A virus-based miRNA suppression (VbMS) system for miRNA loss-of-function analysis in plants

Abstract: MicroRNAs (miRNAs) play key roles in plant development and defense against pathogens. To establish the function of individual miRNAs, gain-of-function analysis is usually done by overexpressing a specific miRNA in transgenic plants and has proved very effective. Loss-of-function analysis by the target mimic method is now also increasingly being used. The mimics expressed in the transgenic plants sequester a specific miRNA and lead to changed phenotypes that elucidate miRNA function. However, it takes time to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The increased sensitivity to salinity stress shown by the GhFSD1silenced plants strongly suggested a role for this gene in the tolerance of cotton to salt stress, although the mechanism is still unknown. Many studies have reported that plant virus-based vectors could be used to study miRNA functions in plants [33][34][35]. When the virus-based vectors carrying precursor sequences of endogenous miRNAs infects the plants, using this viral miRNA expression system, the plant displays the phenotype resulting from the overexpression of that miRNA to investigate the function of miRNAs in plants [36,37].…”
Section: Ghfsd1 and Ghr-mir414c Affect Salt Tolerance Of Cotton By Scmentioning
confidence: 99%
“…The increased sensitivity to salinity stress shown by the GhFSD1silenced plants strongly suggested a role for this gene in the tolerance of cotton to salt stress, although the mechanism is still unknown. Many studies have reported that plant virus-based vectors could be used to study miRNA functions in plants [33][34][35]. When the virus-based vectors carrying precursor sequences of endogenous miRNAs infects the plants, using this viral miRNA expression system, the plant displays the phenotype resulting from the overexpression of that miRNA to investigate the function of miRNAs in plants [36,37].…”
Section: Ghfsd1 and Ghr-mir414c Affect Salt Tolerance Of Cotton By Scmentioning
confidence: 99%
“…Hence, MIMs can inhibit miRNA activity causing loss-of-function miRNA effects (Franco-Zorrilla et al, 2007). Artificial MIMs, and variations thereof, have now been designed as tools to target miRNAs of interest, being stably introduced into the plant via Agrobacterium transformation (Todesco et al, 2010;Yan et al, 2012) or transiently with the use of viral vectors (Sha et al, 2014, Yan et al, 2014, enabling the in vivo functional roles of miRNAs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the association of nbe‐miR166h‐p5 with PVX infection, the expression of this miRNA was suppressed using the Tobacco rattle virus (TRV)‐based miRNA suppression (VbMS) system (Yan et al ., ), and the progress of PVX infection was monitored. For VbMS, a target mimic (TM) sequence that would sequester nbe‐miR166h‐p5 was designed according to the methods described previously and introduced into the TRV vector, producing TRV:TM (Yan et al ., ). TRV:TM or TRV:00 (empty vector control) was inoculated onto plants by agroinfiltration.…”
Section: Resultsmentioning
confidence: 99%